DEVELOPING STUDENTS’ CREATIVE THINKING IN THE PROCESS OF STUDYING PROJECTIVE GEOMETRY - Жунусова, Р.; Bоkayeva, M.; Zhapakova, A. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2026)
This article discusses methods for completing complex geometrical construction tasks to develop students’ creativity. The effectiveness of methods for developing creative qualities such as flexibility, lateral thinking, and a creative approach is noted. It also describes methods for developing students’ creative thinking and creative skills, problem-based learning methods, and students’ research skills. The aim of this study is to improve students’ creative abilities in lectures, practical work, and independent work on projective geometry. In this article, we present methodological methods and approaches aimed not only at teaching but also at developing creative thinking. These methods were applied in the educational process at Margulan University in teaching projective geometry and led to a positive shift in the development of students’ creative thinking.